Dynamic Performance on Multi Storey Structure Due to Ground Borne Vibrations Input from Passing Vehicles - Tuan Chik, Tuan Norhayati; Alexius Asie, Rachel; Wan Ibrahim, Mohd Haziman; Yusoff, Nor Azizi (International Journal of Integrated Engineering, 2013)
Ground borne vibration from passing vehicles could excite the adjacent ground, hence produces a vibration waves that will propagate through layers of soil towards the foundations of any adjacent building. This vibration could affects the structure of the building at some levels and even the low sensitivity equipment are also could be affected as well. The objectives of this study are to perform the structural response on multi storey building subjected to ground vibrations input and to determine the level of vibration at each floor from road traffic on the observed building. The scopes of the study are focused on the groundborne vibrations induced by the passing vehicles and analyse the data by using dynamic software such as ANSYSv14 and MATLAB. The selected building for this study is the Registrar Office building which is located in Universiti Tun Hussein Onn Malaysia (UTHM). The inputs of the vibration were measured by using Laser Doppler Vibrometer (LDV) equipment. By conducting the field measurement, a real input of ground borne vibration from the loads of vehicle towards any adjacent building can be obtained. Finally, the vibration level from road traffic on office building can be determined using overseas generic criteria guidelines. The vibration level achieved for this building is at above the ISO level, which is suitable for office building and within acceptable limit.